The impact of artificial intelligence adoption on firms’ innovation performance in the digital era: based on dynamic capabilities theory - Li, KaiFei; Cai, YuLe; Pei, YuTing; Yuan, ChunHong (International Theory and Practice in Humanities and Social Sciences, 2025)
Based on dynamic capability theory, this study investigates the mechanism through which artificial intelligence (AI) adoption affects firm Using panel data from 634 Chinese listed manufacturing firms during 2018-2023, we find that: (1) AI adoption has a significant positive effect on firm innovation performance; (2) organizational learning capability partially mediates the relationship between AI adoption and firm innovation performance. positive effect on firm innovation performance; (2) organizational learning capability partially mediates the relationship between AI adoption and innovation performance; (3) environmental dynamism positively moderates the relationship between AI adoption and organizational learning capability, such that the positive effect of AI adoption and organizational learning capability is not only on firm innovation performance, but also on firm innovation performance. capability, such that the positive effect of AI adoption on organizational learning capability becomes stronger when environmental dynamism is higher. This study not only enriches the application of dynamic capability theory in the context of digital transformation but also provides important implications for firms to implement AI. This study not only enriches the application of dynamic capability theory in the context of digital transformation but also provides important implications for firms to implement AI strategy and enhance innovation capability.